Ewolucja statusu prawnego dzieci pozamałżeńskich w prawie szkockim (1836–2006) - Mateusz Szymura (Prawo, 2025)
This article concerns the process of redressing the difference in the legal situation of marital and extramarital children in the Scottish legal system. The extent of discrimination against the latter group concerned not only the spheres of their relationship with their father and his family, but also personal private legal rights (such as the right to dispose of property mortis causa by means of a will), as well as public rights. The process, which began in the 19th century, initially had the scope of incremental changes, but ones that paved the way for systemic reform in the 20th century. This in turn lead to the abolition of “illegitimacy” as a characteristic of an individual resulting from the form of his parents’ relationship at the time of conception or birth of the child, which took place in the 21st century, which at that time was in fact a purely symbolic motion. The problem of discrimination against extramarital children is a universal one. At the same time, the way and legal process over which the legal differences in the status of these two groups of children would have been completely eliminated will remain discrete and specific for each legal system.